Epigenome-wide association study of serum urate reveals insights into urate co-regulation and the SLC2A9 locus - Tin, Adrienne; Schlosser, Pascal; Matias-Garcia, Pamela R.; Thio, Chris H. L.; Joehanes, Roby; Liu, Hongbo; Yu, Zhi; Weihs, Antoine; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L.; Kuhns, Victoria L. Halperin; et al. (Nature Communications, 2021)
Elevated serum urate levels, a complex trait and major risk factor for incident gout, are correlated with cardiometabolic traits via incompletely understood mechanisms. DNA methylation in whole blood captures genetic and environmental influences and is assessed in transethnic meta-analysis of epigenome-wide association studies (EWAS) of serum urate (discovery, n = 12,474, replication, n = 5522). The 100 replicated, epigenome-wide significant (p < 1.1E-7) CpGs explain 11.6% of the serum urate variance. At SLC2A9, the serum urate locus with the largest effect in genome-wide association studies (GWAS), five CpGs are associated with SLC2A9 gene expression. Four CpGs at SLC2A9 have significant causal effects on serum urate levels and/or gout, and two of these partly mediate the effects of urate-associated GWAS variants. In other genes, including SLC7A11 and PHGDH, 17 urate-associated CpGs are associated with conditions defining metabolic syndrome, suggesting that these CpGs may represent a blood DNA methylation signature of cardiometabolic risk factors. This study demonstrates that EWAS can provide new insights into GWAS loci and the correlation of serum urate with other complex traits.